Lithium‐Niobate–Silica Hybrid Whispering‐Gallery‐Mode Resonators. (16th November 2015) - Bo, Fang; Wang, Jie; Cui, Jiao; Ozdemir, Sahin Kaya; Kong, Yongfa; Zhang, Guoquan; Xu, Jingjun; Yang, Lan
Abstract : Lithium‐niobate–silica hybrid resonators with quality factors higher than 10 5 are fabricated by depositing a layer of polycrystalline lithium niobate on the flat top surfaces of inverted‐wedge silica microdisk resonators. All‐optical modulation with improved performance over silica‐only resonators and electro‐optic modulation not achievable in silica‐only resonators are realized in the hybrid resonators.